Legal Arguments and Linguistic Arguments: When the Language in Use Reveals Prejudices - Valerio, Daiane; Forneck, Kári Lúcia (Lingüística y Literatura, 2021)
Based on the theory of argumentation in language, this work studied the legal argumentation under the principles of linguistic argumentation, in sentences of crimes committed against women, to evidence if there were indications of possible remnants of biased enunciation. The last ten sentences judged for each year (2014-2018) were requested from a district court from the state of Rio Grande do Sul (Brazil). Through the analysis of the argumentative chains, it was possible to reach an interface between linguistic and legal arguments, showing utterances and enunciators that still end up propagating prejudiced discourses against women